Development of deep learning-based classification models for opacity differentiation in pediatric chest radiography - Germán Enrique Galvis Ruiz; Johana Benavides-Cruz; Daniela Muñoz Corredor; Esteban Morales-Mendoza; Héctor Daniel Alejandro Cotrino Palma; Andrés Cely-Jiménez (Informatics in Medicine Unlocked)
Opacities of non-interstitial origin in a pediatric patient's chest radiograph may indicate either consolidations and/or atelectasis, based on the appropriate clinical context. However, the overlapping and complex symptomatology of respiratory tract diseases in pediatric patients can make it difficult for physicians to interpret opacities. Artificial intelligence models are frequently employed by physicians for diagnostic support in healthcare, especially to evaluate aspects of radiographs that are not visible with the naked eye. In this study, a prediction model based on deep learning was used to differentiate between atelectasis and consolidations in pediatric chest radiographs from a clinical perspective. The radiologist can assist pediatricians in diagnosing respiratory pathologies based on the type of opacities using the machine learning model. We used 1297 chest X-ray images of pediatric patients with opacities including consolidations (n=500), atelectasis (n=499); and images without opacities (n=298). The images were preprocessed, and various deep learning models were applied to determine the model with the best metrics. The InceptionV3 model demonstrated a significant improvement over its initial results.